Descriptions of the new species of the genus Nepalmatoiulus Mauriès, 1983 from China, with notes on the closely coexisting species (Diplopoda, Julida, Julidae) - Mikhaljova, Elena V. (Zootaxa, 2023)
Three new closely coexisting species of the millipede genus Nepalmatoiulus Mauriès, 1983 are described from China: Nepalmatoiulus alternus sp. nov. and Nepalmatoiulus simultaneus sp. nov. from Laojunshan, as well as Nepalmatoiulus tuoxiaensis, sp. nov. (coexisting species is Nepalmatoiulus parvulus Mikhaljova, 2020) from Deqin. Their sympatry and coexistence are discussed. Morphological variability of the anterior gonopods in two of the new species is revealed.